2018
DOI: 10.1007/978-3-030-00934-2_55
|View full text |Cite
|
Sign up to set email alerts
|

Factorised Spatial Representation Learning: Application in Semi-supervised Myocardial Segmentation

Abstract: The success and generalisation of deep learning algorithms heavily depend on learning good feature representations. In medical imaging this entails representing anatomical information, as well as properties related to the specific imaging setting. Anatomical information is required to perform further analysis, whereas imaging information is key to disentangle scanner variability and potential artefacts. The ability to factorise these would allow for training algorithms only on the relevant information accordin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…The decomposition process yields representations for the anatomy and the modality characteristics of medical images and is achieved by two dedicated neural networks. Whilst a decomposition could also be performed with a single neural network with two separate outputs and shared layer components, as done in our previous work [Chartsias et al, 2018], we found that by using two separate networks, as also done in and in Lee et al [2018], we can more easily control the information captured by each factor, and we can stabilise the behaviour of each encoder during training.…”
Section: Input Decompositionmentioning
confidence: 96%
See 1 more Smart Citation
“…The decomposition process yields representations for the anatomy and the modality characteristics of medical images and is achieved by two dedicated neural networks. Whilst a decomposition could also be performed with a single neural network with two separate outputs and shared layer components, as done in our previous work [Chartsias et al, 2018], we found that by using two separate networks, as also done in and in Lee et al [2018], we can more easily control the information captured by each factor, and we can stabilise the behaviour of each encoder during training.…”
Section: Input Decompositionmentioning
confidence: 96%
“…It is interesting to compare the performance of SDNet with our previous work [Chartsias et al, 2018]. We therefore modify our previous model for multi-class segmentation and repeat the experiment for the ACDC dataset.…”
Section: Semi-supervised Segmentationmentioning
confidence: 99%
“…Unsupervised task Bai et al (2017) Embedding consistency Zhang et al (2017b) Image classification Sedai et al (2017) Image reconstruction Baur et al (2017) Manifold learning Chartsias et al (2018) Image reconstruction Huo et al (2018a) Image synthesis Zhao et al (2019) Image registration Li et al (2019) Transformation consistency the same-class pixels as close as possible while pushing apart the feature embedding of the pixels from different classes. To identify same-class pixels between labeled and unlabeled images, the authors assume the availability of a noisy label prior for unlabeled images.…”
Section: Publicationmentioning
confidence: 99%
“…For the task of gland segmentation in histopathology images, the authors have demonstrated one point increase in Dice over fully-supervised models trained with labeled data. Chartsias et al (2018) propose a solution to the problem of domain shift based on a disentangled image representation where the idea is to separate information related to segmenting the structure of interest from the other image features that readily change from one domain to another. By doing so, the segmentation network focuses on the intrinsic features of the target structure rather than variations related to imaging scanners or artifacts.…”
Section: Publicationmentioning
confidence: 99%
“…An increased interest in SSL has also been seen in medical image anlaysis. The use of an unsupervised representation learning for better generalization has been investigated for the task of myocardial segmentation [2]. In [10], SSL was used in a similar X-ray data set, although the scope was limited to binary classifications between normal and abnormal categories.…”
Section: Related Workmentioning
confidence: 99%